Evaluation of pulp vitality using a pulse oximeter in patients undergoing radiotherapy for rhabdomyosarcoma or rhinopharynxcarcinoma (Research, Society and Development, 2021)
The oral cavity is highly susceptible to pathological changes due to the deleterious effects of radiation (RI) on tissues exposed during radiotherapy (RT). The aim of this study was to evaluate the feasibility of using pulse oximeter (PO) as a diagnostic instrument for assessing the pulp oxygenation level (%SpO2) of immature teeth previously exposure to IR. Pulp oxygenation saturation was evaluated in fifteen children or adolescent patients (Group RT) that received previous IR, 6.01 years ago (SD 4.08 years), and fifteen patients without a history of neoplasms or previous chemotherapy or radiotherapy (CO group). As result, the mean %SpO2 measured in Group RT and Group CO was 86.06% (SD 1.61%) and 91.11% (SD 0.87%), respectively. Conclusions: The use of the pulse oximeter adapted for dentistry for pulpal vitality evaluation in patients who received radiotherapy is feasible showing lower level of SpO2 than that of the control group (p